Pencegahan Dampak Negatif Pinjaman Online Ilegal dan Judol melalui Edukasi Literasi Digital dan Pemanfaatan Artificial Intelligence di Pondok Pesantren La Tansa Palembang - Dwi Noviani; Hilmin Hilmin; Hairun Nisa; Choiriyah Choiriyah; Tegar Ash Shiddiq (Lembaga Pengembangan Kinerja Dosen, 2026)
The acceleration of digitalization in recent years has shaped a new socio-economic landscape in Indonesia. Access to app-based financial services and online entertainment has increased rapidly, but at the same time, illegal online lending and digital gambling, targeting adolescents, have flourished. This paper explores a Community Service intervention model that combines preventative digital literacy and artificial intelligence (AI) optimization within the La Tansa Islamic Boarding School in Palembang. The research was conducted using a qualitative approach with participant observation, in-depth interviews, focus group discussions, and written reflection analysis. Findings indicate that strengthening digital literacy based on critical awareness not only improves risk understanding but also deepens self-control integrated with religious values. AI training for educators also encourages changes in learning practices to be more adaptive and reflective of the dynamics of the digital era. This model offers a digital resilience approach that can be replicated in other educational institutions with similar characteristics.